Progress towards elimination of onchocerciasis in the Region du Sud-Ouest of Burkina Faso which was previously subject to a recrudescence event after vector control. - Achille Sindimbasba Nikièma; Lassane Koala; Rory J Post; Appolinaire Kima; Justin Compaoré; Claude M Kafando; Jean Baptiste Nana; Clarisse Bougouma; Babacar Faye; Soungalo Traoré; Roch Kounbobr Dabiré (Public Library of Science (PLoS), 2024)
Background The Sud-Ouest region of Burkina Faso (especially the Bougouriba valley) has been historically problematic with respect to onchocerciasis control, with a recrudescence of infections after vector control carried out the WHO Onchocerciasis Control Programme was halted in 1989. After 1996, mass drug administration of ivermectin was instigated to control the recrudescence so that it would no longer constitute a public health problem. However, in 2010 WHO changed its recommended policy from control to elimination, and in 2013 biannual Community-Directed Treatment with Ivermectin (CDTI) was instigated. Epidemiological surveys were carried-out in 2011 and 2018 to determine whether CDTI was producing a decline in infection levels and progress towards elimination. Methodology/principal findings A cross-sectional study was conducted across 20 villages in four health districts in 2011 and 29 villages in 2018. Individuals aged five years and above were examined by skin-snip, and the prevalence and microfilarial load was determined for each village. In 2011, 75% of villages had some infections and 20% had prevalences >5%, with a mean prevalence across all villages of 2.63% (range 0.0-9.7%), and community microfilarial load ranging from 0 to 0.25 microfilariae per biopsy. In 2018, nine villages (= 31% of total) had some infections, with prevalences ranging from 0.41% to 3.54%, and a mean prevalence across all villages of 0.37%. Community microfilarial load ranged from 0 to 0.1. Amongst those people found to be microfilarial positive, 87% had a history of migration. Conclusions/significance The endemicity of onchocerciasis infection in the Sud-Ouest region has declined to low levels and seems to be progressing towards elimination. Our findings indicated that biannual CDTI is having good effect, but it should continue for a number of years to ensure elimination of transmission. However, progress towards elimination has a troublesome history in this region, and it would be advisable to select more sentinel villages to have confidence in any future epidemiological and entomological surveys, especially Stop-MDA surveys. With positive individuals migrating between countries, cross-border collaboration needs more attention to ensure effective treatment for onchocerciasis elimination.